Wpływ języka angielskiego na język polski jako przedmiot rozważań polityki językowej = The impact of English on Polish from the perspective of language policy - Karczewska, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The object of the discussion is the impact of English on other languages, with special attention paid to Polish, as well as on the issue of language policy towards Anglicisms. Theoretical reflections are then collated with the results of a survey conducted among foreign languages students at the University of Zielona Góra in which the respondents answered, among others, a question about possible threats resulting from the dominance of English in today`s world.
Keywords: polityka językowa; anglicyzmy; angielski jako język globalny; language policy; Anglicisms; global English